The Influence of Family Factors on Emotional Intelligence in ABK - Oktavia, Oktavia; Aprianif, Aprianif (PT. BATARI EDU CALYA, 2024)
This study aims to analyze the influence of family factors on the emotional intelligence of children with special needs (ABK) at Al Ihsan 01 Special School in South Tangerang. Emotional intelligence is measured as the dependent variable, while the independent variables in this study include gender, child’s age, family economic factors, mother's age during pregnancy, parental education, and the presence of a special assistant. Data was collected through questionnaires distributed to parents and interviews with teachers, based on Goleman’s (2009) emotional intelligence indicators. The results of this study are expected to provide a deeper understanding of the role of family factors in the development of emotional intelligence in children with special needs and offer recommendations for more effective educational strategies in special schools